O Carimbó é do carimbó: culturaS, sabereS e políticaS - BOGÉA, Eliana Benassuly (Universidade Federal do Pará, 2020)
The Federal Constitution of 1988, as the Regulatory Framework for the Redemocratization of Brazil, gives shape to our work through the free appropriation of the organization of this legal text to hold debates of our time. In this perspective, we present our problem in “giras/rodas de Carimbó” as we experienced the process of construction of the thesis in approximately ten years of living the Carimbó organized social movement that motivated us to understand/question the identified internal/external conflicts and whose our concern was to see the people, women/men of Carimbó, that remain CarimbozeirXs even when out of the scene. Thus, our theoretical framework goes beyond the object of research to recognize a Carimbozeiro corpus and, with that, coining what we call the field of cultures and in this social space identify/disentangle cultures as rights before/during a post-coup 2016 Brazil. In the Title III Do Carimbó, we go through the knowledge and policies from inside and outside the scene, meaning that Xs carimbozeirXs interests us more than the Carimbó artistic expression and cultural manifestation widely treated in other scientific works. Our final “gira/roda” takes Master Verequete da Coluna to echo hopes that our work will contribute to understanding and acting in a Brazil and in a planet that progressively tends to transform us as foreigners to ourselves.